Answer:
The given statement is true.
Explanation:
An inverse function can be defined as a function that "reverses" another function: if the function f applied to an input x gives a result of y, then applying its inverse function g to y gives the result x, and vice versa, i.e., f(x) = y if and only if g(y) = x.
Examples are x+2 and x-2
WE get f(x) = x+2
Apply g(x) = g(f(x))=g(x+2)
=x+2-2=x
Thus by applying composiiton g f or fg in any order we get the answer as x
THis is the property of any inverse function